Saccharomyces boulardii CNCM I-745 supplementation during and after antibiotic treatment positively influences the bacterial gut microbiota - Spatz, Madeleine; Wang, Yazhou; Lapiere, Alexia; Da Costa, Gregory; Michaudel, Chloé; Danne, Camille; Michel, Marie-Laure; Langella, Philippe; Sokol, Harry; Richard, Mathias L. (Frontiers in Medicine, 2023)
Introduction Antibiotic effects on gut bacteria have been widely studied, but very little is known about the consequences of such treatments on the mycobiota, the fungal part of the microbiota and how the length of administration influences both microbiota. Here, we examined the effect of antibiotics (ATB) on the composition of bacterial and fungal microbiota and how the administration of Saccharomyces boulardii CNCM I-745 influences both microbiota. Methods In order to get closer to the human microbiota, the mice used in this study were subjected to fecal microbiota transfer (FMT) using human feces and subsequently called human microbiotaassociated (HMA) mice. These mice were then treated with amoxicillinclavulanate antibiotics and supplemented with S. boulardii during and after ATB treatment to understand the effect of the yeast probiotic on both bacterial and fungal microbiota. Bacterial and fungal microbiota analyses were done using 16S and ITS2 rRNA amplicon-based sequencing. Results We showed that the administration of S. boulardii during ATB treatment had very limited effect on the fungal populations on the long term, once the yeast probiotic has been cleared from the gut. Concerning bacterial microbiota, S. boulardii administration allowed a better recovery of bacterial populations after the end of the ATB treatment period. Additionally, 16S and ITS2 rRNA sequence analysis revealed that 7 additional days of S. boulardii administration (17 days in total) enhanced the return of the initial bacterial equilibrium. Discussion In this study, we provide a comprehensive analysis of how probiotic yeast administration can influence the fungal and bacterial microbiota in a model of broad-spectrum antibiotherapy.